Construction of coherence in the comprehension of narratives: Studies on the importance of the establishment of causal connections, gaps in current research and future directions - Jazmín Cevasco; Karen Acosta Buralli (Papeles del Psicólogo, 2023)
The establishing of causal connections is key to the construction of discourse coherence. The aim of this narrative review is to present research that has examined the establishment of these connections in the construction of narrative discourse coherence, in order to highlight gaps in current research and suggest future directions. Among these gaps, we will highlight that prior research has not tended to examine the role of the modality of presentation of the materials, or to present spontaneous discourse, or materials about current social problems. In order to review these topics, we introduce the causal chain model, causal network model, causal inference maker model, landscape model, and contributions from constructionist theory and the event-indexing model. We also present studies that support their claims. Finally, we present conclusions and discuss future directions. The presentation of these studies will allow us to underscore the crucial need for research to examine the comprehension of discourse that students process in academic settings, everyday interactions, and that focuses on relevant current social issues.